THE VARIETIES OF QUR’ANIC STYLISTIC EXPRESSION (USLUB) AS A QUR’ANIC COMMUNICATION STRATEGY FROM THE PERSPECTIVE OF BALAGHAH - Melisa Rezi; Asrina Asrina; Syofyan Hadi (Lingeduca: Journal of Language and Education Studies, 2026)
This article discusses the varieties of Qur’anic stylistic expression (uslub) from the perspective of balaghah. The study is grounded in the importance of understanding the linguistic distinctiveness of the Qur’an not merely as a form of literary beauty, but also as a Qur’anic communication strategy that possesses semantic power, rhetorical force, and spiritual influence. This research employs a library research method using a descriptive-analytical approach. The data were obtained from relevant literature on ulumul Qur’an, balaghah, and Qur’anic stylistics. The findings indicate that the varieties of Qur’anic stylistic expression can be understood in multiple layers. The first layer relates to modes of delivery, such as uslub ‘ilmi, uslub adabiy, uslub khithaby, uslub iltifat, and uslub al-hakim. The second layer includes forms of expression, such as amtsal, jadal, aqsam, and qashash. The third layer comprises rhetorical devices in balaghah, such as ijaz, ithnab, musawah, isti‘arah, tasybih, and kinayah. This study affirms that the Qur’anic style does not function merely as verbal ornamentation, but operates as a Qur’anic communication system that integrates clarity, beauty, argumentation, politeness, and depth of meaning.